DEPRESSION AS THE IMPACT OF UNFULFILLED DESIRE IN THE NOVEL SENSE AND SENSIBILITY BY JANE AUSTEN - Siti Nurlaili; Prautomo, Adi (Prologue: Journal on Language and Literature, 2024)
This study focuses on unfulfilled desires that cause depression in the novel Sense and Sensibility. There are two problem formulations in this study, namely 1) to find out the forms of unfulfilled desires in the novel Sense and Sensibility and; 2) to find out the impact of depression due to unfulfilled desires in the novel Sense and Sensibility. The theory used in this research is an analysis of the literary psychology approach using the dream interpretation theory of Sigmund Freud; Based on the study's results, the researcher found several forms of unfulfilled desires through the interpretation of dreams from Sigmund Freud: desire fulfillment, regression, and conscious and unconscious.